Taxonomic revision of Silene (Caryophyllaceae) sections Siphonomorpha, Lasiostemones, Sclerocalycinae, Chloranthae, Tataricae, and Otites in Turkey - (:unkn) unknown (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2013)
Forty-four Silene L. taxa belonging to the sections Siphonomorpha Otth, Lasiostemones Boiss., Sclerocalycinae Boiss., Chloranthae Rohrb., Tataricae Chowdhuri, and Otites (Adams.) Otth were studied. The Silene specimens used in the study were collected from different localities between 2005 and 2007. Their conservation status, phytogeographical regions, and distribution in Turkey were determined. Detailed drawings of the general view and flower from each species were added to the study. As a result of these detailed investigations, the conditions of some species having taxonomic problems were re-examined, and suggestions were proposed. The results produced 3 taxa that are new to science and 2 taxa that are new records for the flora of Turkey. In addition, 5 species that were published as new species from Turkey were reduced to synonyms.
Keywords: Turkey; revision; Silene; systematic; POLLEN MORPHOLOGY; L. CARYOPHYLLACEAE; NOV CARYOPHYLLACEAE; EAST ANATOLIA; GENUS SILENE; FLORA